A dual-channel detection of mercuric ions using a label free G-quadruplex-based DNAzyme molecule. Issue 13 (20th May 2016) - Ma, Long; Liu, Haiyan; Wu, Guanrong; Sun, Nana; Meng, Lingpei; Li, Yuyin; Liu, Zhenxing; Diao, Aipo
Abstract : We have constructed a 'turn-off' and label free bio-sensor using a DNAzyme molecule. Abstract : We have constructed a 'turn-off' and label free bio-sensor using a DNAzyme molecule. This facile bio-sensor is capable of selective detection of mercuric ions with a high sensitivity and satisfactory dynamic range. More importantly, it is able to generate both fluorescent and colourimetric signals for detection. This dual-channel bio-sensor is expected to afford high detection confidence and overcome false-positive readout especially when assaying complex biological samples.